The Development And Advantages Of Xstrata?s Premus Process - O. Naiker (The Southern African Institute of Mining and Metallurgy, 2007)
Xstrata has modified and improved on the solid state reduction of chromite (SRC) process that was pioneered by Showa Denko in Japan and previously used at Xstrata?s Lydenburg plant. The history of pre-reduction is a long one, with the SRC process being the first and only commercially successful one prior to Premus. Krupp developed the chromite direct reduction and the rotary hearth for the pre-reduction of chromite. However, these processes have not been successfully commercialised. The are a number of significant differences between Xstrata?s patented Premus and the original Consolidated Metallurgical Industries (CMI) process. These include, the use of lower cost anthracite fines as the reductant source together with the use of unactivated bentonite as the binding agent. In addition the use of oxygen as an energy source is used in Premus but not in the original CMI process. There was a fundamental change in the operational philosophy of the process in that while the original CMI process aimed to maximize metallization of the pellets, the Premus process seeks to maximize the energy output from the kiln while still achieving the required efficiencies and hence increasing furnace output. Premus is designed to reduce electrical energy consumption, provide high recoveries of metallic oxides, and utilizes low cost reductant and energy sources such as anthracite and oxygen respectively. Due to the fact that Premus is one of the most technologically advanced and competitive processes used today in the production of ferrochrome it was the process selected for Xstrata?s new ferrochrome facility, Project Lion, that is due to be commissioned in the third quarter of 2006 in the Steelpoort Valley in Mpumulanga, South Africa.